Managing and integrating extended supply chains web services to the rescue. - Madhavanur, Desikan (SOA webservices journal.)
Over the last decade, supply chains have evolved to keep pace with changing business dynamics. This is especially true in high-tech electronics, where companies depend on an extended value chain of component suppliers, outsourced manufacturers and logistics partners-not to mention B2B-integrated customers- to coordinate vital inter-company design and manufacturing processes. Adding to this complexity, business decisions are more centralized, while outsourced supply networks are increasingly distributed and global.